Solitary pancreatic metastasis of gastric cancer with synchronous pancreatic ductal carcinoma: A case report. (2020) - Yokoyama, Yuichiro; Sakata, Hiroki; Uekusa, Toshimasa; Tajima, Yusuke; Ishimaru, Masahiro
Highlights: Solitary pancreatic metastasis of gastric cancer is rare. Favourable survival after surgical resection of solitary pancreatic metastasis. Low frequency of pancreatic duct dilation in solitary pancreatic metastasis. Pancreatic metastasis of gastric cancer with primary pancreatic cancer can occur. Abstract: Background: There have been a few reports on solitary pancreatic metastases of gastric cancer. We present a case of solitary pancreatic metastasis of gastric cancer with synchronous primary pancreatic ductal carcinoma. Presentation of Case: An 86-year-old man who had undergone total gastrectomy two and half years prior presented with a poorly enhanced tumor in the pancreatic body. We diagnosed pancreatic ductal carcinoma and performed distal pancreatosplenectomy. Histopathologically, the tumor comprised poorly differentiated adenocarcinoma cells mixed with moderately differentiated tubular adenocarcinoma cells that were compatible with metastasis of gastric cancer. There was also invasive ductal carcinoma of the pancreas. The postoperative course was uneventful. Six months after surgery, computed tomography revealed peritoneal dissemination, and he died of recurrence 10 months after surgery. Conclusion: Pancreatic metastasis of gastric cancer with synchronous primary pancreatic cancer can occur and should be considered in the differential diagnosis.